Upaya Penanganan Cyberbullying di Media Sosial: Studi Perbandingan antara Indonesia dan Korea Selatan - Silvyana, Anastasia; Zefanya, Bintang; Nurpadilah, Fitri Hasanah; Nurhaliza, Jasmine; Putri, Tiara Sukmana; Nazirah, Nazirah; Rudiana, Rudiana (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Cyberbullying or online bullying has become an alarming global phenomenon, especially in the current digital era. This study discusses and compares the policies and approaches implemented by Indonesia and South Korea in handling cyberbullying cases. The comparative descriptive approach used in this research collects data from various secondary sources, including scientific literature, research reports, and legal and policy documents. Policies for handling cyberbullying are regulated through the Information and Electronic Transactions Law as well as several additional regulations, although they still face challenges in effective and consistent implementation. Meanwhile, South Korea relies on several key legal products and an inclusive approach, although its regulatory implementation also faces challenges. Both countries have their own complexities in dealing with cyberbullying, which are influenced by social, cultural and technological factors. The results of this research emphasize the importance of inter-agency coordination, improvements in legal definitions, and increased public awareness as keys to increasing victim protection and reducing future cyberbullying incidents.